ソウヤカイガン ノ リュウキ カイセイ タイセキブツ カラ エラレタ カイカセキ ノ 14Cネンダイ JARE-35 (1993-94) ノ シリョウ - 平川, 一臣; ヒラカワ, カズオミ; 澤柿, 教伸; サワガキ, タカノブ; Hirakawa, Kazuomi; Sawagaki, Takanobu (1998)
P(論文) 第35次日本南極地域観測隊の野外調査において, 宗谷海岸の隆起海成堆積物から貝化石を採取し, そのうちの40試料から放射性炭素年代を得た。その結果, それらは3-8kaの完新世の年代を示すものと, 35ka以上の年代を示すものとに分けられた。これまでの研究ではラングホブデから古い年代が多く得られているが, 今回の測定では, 完新世の年代値は全調査地域に分布するのに対し, 古い年代値を示すものはオングル諸島に限られる。オングル諸島では古い年代値をしめす貝化石は標高20m付近まで分布し, 新しい年代値を示す貝化石より高位置まで分布する。スカレビークハルセンおよびルンドボークスヘッタからは, 初めて放射性炭素年代が得られた。 40 Radiocarbon ages are obtained from fossil shells collected from raised beach deposits along the Soya Coast, East Antarctica during the summer season of JARE-35,1994. They are clearly classified into younger Holocene dates of 3ka to 8ka and dates older than 35ka. The older dates are restricted to shells from the Ongul Islands, while the younger ones were found in all outcropped areas, although older dates had been reported from Langhovde in previous studies. Older shells in the Ongul Islands are distributed at higher elevation up to 20m above present sea level than younger shells. The highest elevation of a Holocene raised beach attains 26m above sea level in Skarvsnes. This is the first report of radiocarbon dates from Skallevikhalsen and Rundvagshetta. departmental bulletin paper